Interactive Paths in Viewpoints: Notes and Inflections in "Seven Tones of Poetry" (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article, describe a process of creation in dance, based on theoretical/practical studies, under the co-evolutionary bias of understanding the body as a media of itself, supported by the Teoria Corpomídia, by the method developed by the North American director Anne Bogart, the Viewpoints are based on the classroom experience with young residents of the Alto de Santa Cruz neighborhood.  These young people, marked by violence and daily deaths, and the precarious reality of the public school teacher, are references to the assembly of the work Seven Tons of a Poetry.  This  writing, present personal inferences as an artist and teacher in the Municipal Network of Salvador, which understands both as political action, whose focus is on singular and local issues.
Keywords: Viewpoints; Dance; Education; Teacher; Teoria Corpomídia